2014
DOI: 10.1007/s40141-014-0054-1
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Spinal Cord Injury

Abstract: Traumatic spinal cord injury (SCI) occurs much less commonly in children than adults. Children can also experience spinal cord dysfunction from birth injuries, skeletal dysplasias, neoplasms, infections, and autoimmune causes. There are special considerations for determining the level and completeness of injury in children under 6 years of age. Children with SCI experience some unique secondary complications such as scoliosis, and other complications such as autonomic dysreflexia require modifications in manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 92 publications
0
5
0
1
Order By: Relevance
“…The most common non-traumatic causes of SCIs include neoplasms or spinal cord tumors that can be either benign or malignant and lead to compression of the spinal cord, resulting in an SCI without direct trauma. Aside from tumors, transverse myelitis is another common cause of non-traumatic SCI in children, involving the inflammation of both sides of the spinal cord, often leading to damage to myelin and resulting in impairments in nerve signals [ 5 ]. Compared to adults, neurological recovery following an SCI is reported to be better in pediatric populations.…”
Section: Pediatric Sci Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The most common non-traumatic causes of SCIs include neoplasms or spinal cord tumors that can be either benign or malignant and lead to compression of the spinal cord, resulting in an SCI without direct trauma. Aside from tumors, transverse myelitis is another common cause of non-traumatic SCI in children, involving the inflammation of both sides of the spinal cord, often leading to damage to myelin and resulting in impairments in nerve signals [ 5 ]. Compared to adults, neurological recovery following an SCI is reported to be better in pediatric populations.…”
Section: Pediatric Sci Epidemiologymentioning
confidence: 99%
“…A pediatric SCI differs from its adult counterpart in several key aspects. Anatomically, the developing pediatric spinal cord exhibits distinct structural characteristics with different response mechanisms to injury [ 1 , 5 ]. The pediatric spinal cord is more pliable and elastic, leading to different injury patterns and the potential for recovery compared to adults.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric spinal cord injury has several significant distinguishing features that are related to the tissue maturation stage of the child’s spinal cord and the disparity in size between the child and an adult. There is a variability in the structural and morphologic features of the growing pediatric spinal cord, and the changes in it differ after injury as well [ 7 ]. Safe for teenagers (adolescents) to participate in it, because it is more pliable and elastic, leading to different types of injuries and the potential to heal differently, compared to adults.…”
Section: Introductionmentioning
confidence: 99%
“…From these studies, the figure has shown that up to 90% of these impacts do not influence severe injuries and people can go home. Nevertheless, 37,000 cases need hospitalization, and 2,685 people pass away as a result of their injuries [2,4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Paediatric spinal cord injury (SCI) accounts for only 1–13% of all reported SCI cases [1, 2], but spinal injury has a long and lasting impact on quality of life for these children. While it is acknowledged that children may be more vulnerable to severe injuries, if they survive an injury of comparable force, they appear to have a different, often better and faster recovery than their adult counterparts.…”
Section: Introductionmentioning
confidence: 99%